Creating a Dashboard to Track Progress Toward IOM Recommendations for the Future of Nursing. (August 2013) - Spetz, Joanne; Bates, Timothy; Chu, Lela; Lin, Jessica; Fishman, Nancy W.; Melichar, Lori
This article explains the process used to identify and develop a set of data used to track national progress toward the recommendations of the Institute of Medicine Committee for the Future of Nursing. The data are presented in a dashboard format to visually summarize information and quickly measure progress. The approach selected by the research team is outlined, the criteria for selecting candidate metrics are detailed, the process for seeking external guidance is described, and the final dashboard measures are presented. Finally, the methods for data collection for each metric are explicated, to guide states and local regions in the collection of their own data.